Miru-vntr technique for molecular epidemiological studies of tuberculosis - E. V. Аntusheva; I. V. Tarasova; P. I. Eliseev; A. O. Mariandyshe (Туберкулез и болезни лёгких)
Goal of the study: to study the efficiency of using MIRU-VNTR molecular genetic technique for molecular epidemiological studies among pulmonary tuberculosis patients.Materials and methods: 20 patients with pulmonary tuberculosis relapses, 12 pulmonary tuberculosis patients with hetero-resistant results of drug susceptibility testing, 7 patients who developed tuberculosis during staying in a medical social unit, one adult and one child exposed to tuberculosis in their families with doubtful correlation between their diseases. The genetic pattern of M. tuberculosis strains for MIRU-VNTR 9-10 loci have been compared.Results. 55% of tuberculosis relapses are related to infection with a new M. tuberculosis strain, the remaining cases belong to re-activation of the endogenous strain of M. tuberculosis. In case of hetero-resistant results of DST the mixed infection with two strains of M. tuberculosis was found only in 1 (8.3%) out of 12 patients, in the remaining cases M. tuberculosis belonged to the one genotype but with different resistance patterns. Contact tracing of tuberculosis break-out (7 patients) in the closed medical social unit proved the presence of several sources of the infection. Contract tracing of the family exposure proved the actual infection transmission in the family and the source of the infection was identified.